Development of Game AR Integrated PjBL Syntax of Earth Structure Materials to Improve Students Creative Thinking Skills - Sudarmin, Sudarmin; Khamida Hikmawati; Hardianti, Risa Dwita; Parmin, Parmin; Lestari, Endang Sri (Universitas Negeri Semarang, 2024)
Creative thinking is one of the competencies that must be possessed in the 21st. However, there is a problem that students' creative thinking skills need to be improve, educational games needs to be improved due to the lack of adjustment of learning media with the condition of students. Therefore, Game AR media integrated with the PjBL syntax is needed that can improve students' creative thinking skills. This study aims to develop a valid Game AR media integrated with the PjBL syntax and analyze the significance of the influence of Game AR media integrated with the PjBL syntax on improving students' creative thinking skills. The research was carried out at SMP Negeri 1 Nusawungu. The population in this study is all class VIII and the sampling technique is carried out by means of cluster random sampling. The sample of this study is 31 students in class VIII A SMP Negeri 1 Nusawungu. This research uses the Research and Development method with a 4D model (Define, Design, Development, Disseminate). The results of the study show that the PjBL integrated Game AR is valid to be used with the N-Gain value of students in the high category. The results of the paired sample t-test showed a significance value < probability, so that it can be concluded that the Game AR media integrated with the PjBL syntax developed is valid to use and can significantly improve students' creative thinking skills.